Conceptual framework of integrated sustainable community based homestay in malaysia - Wan Abd Aziz, Wan Mohd Amin (2015)
A Model of Integrated Rural Tourism plays significant roles to sustain the Community Based Homestay in Malaysia. The Integrated Rural Tourism took account various resources (cultural,social,environment and economy) to integrate into various stakeholders in order to promote Homestay development. Thus, this paper will discuss the concept of Integrated Rural Tourism and Model of Integrated Rural Tourism that will be useful to long term sustainability of Community Based Tourism.